Agricultural equipment displays - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows some tractors and plows in a tented display area. Hanging signs read, "Cletrac Tank Type Tractor for Farm and Industrial Uses, The Cleveland Tractor Co., Cleveland, Ohio, USA"; "Dean Tractor and Implement Co., Sales - Service, 269 W. Santa Clara St., San Jose"; Knapp Plow Co., Inc., San Jose"; and "Parrish [illegible] Cupertino". A variety of banners hang from the ceiling of the tent.